KOMPETENSI AWAL PESERTA DALAM MATA DIKLAT TEKNIK PRESENTASI BERBASIS MULTIMEDIA - Losarini Sumartati (Tatar Pasundan: Jurnal Diklat Keagamaan, 2019)
This study aims to determine the initial competency description of the functional training participants of the young teacher class XIII 2018. The research method used is descriptive method with a research instrument in the form of a closed questionnaire given to all training participants totaling 30 people, taking place on 9 October 2018. The distribution of questionnaires was conducted at the beginning of learning because it aims to find out the initial competency of the training participants before learning begins. The questions asked in this closed questionnaire are questions that must be answered by the training participants with answers "YES" or "NO". This closed questionnaire was distributed to the class group of training participants using Google form. From 30 training participants who sent back the questionnaire to 25 people, this number was the basis for subsequent data processing. The data obtained are processed simply in the form of a percentage for each aspect of the question. The results showed that the initial competency of the 2018 Young Teachers Functional Training participants for the ten aspects for the ten aspects had the lowest average "YES" for the aspect of navigation in PowerPoint (27.00%), which was more detailed for question number 40 namely about skills in using menus and navigation (76%), following the next two that have not been mastered namely the skills to use hyperlinks (72%) and presentations with slide masters (72%). Whereas for the aspect that has the highest average percentage of "YES" is knowing PowerPoint (85.32%), the next downturn is working with text in PowerPoint {more in detail to question number 13 about writing text in the text box (84%)}, and techniques for preparing presentations {in more detail to question number 12 about reducing existing slides (80%)}. The data obtained can be used as material to organize strategies in learning. Key Words: Pre Competences, Training, Multimedia